PRACTICAL FIELD INVESTIGATION TO INDICATE COMMON FLEXIBLE PAVEMENT DISTRESSES THAT OCCUR IN THE MALIK MAHMOOD RING ROAD-SULAIMANIYAH CITY - AHMED, HEMN UNIS; ABDULLAH, WRYA A.; OMAR, SARDAR MAJEED; ALSHKANE, YOUNIS M.; MAHMOOD, ARIAN OMER (Journal of Duhok University, 2020)
When the top layer of the road defects with time, it is called distresses of the pavement. The causes for this pavement distress vary as most of the flexible pavement structures are subjected to repeated heavy traffic loadings and high temperature changes which causes pavement cracking, deformation and deterioration. The existence of these defects on the road surface makes it uncomfortable and unsafe for the users, therefore, it should be determined and treated in appropriate ways. This research is conducted to identify the most common types of flexible pavement distresses which occur in the Sulaimaniyah city, Iraq, and to find out different reasons behind those distresses along with proposing suitable ways for theirmaintenance. The data collection was done in the Malik Mahmood ring road in the Sulaimaniyah city. The work study is carried out in locations that are subjected only to passenger cars and heavy truck loadings. Field surveying shows that the most common flexible pavement distresses occurred in the selected area are various types of cracking, rutting, corrugation, shoving, patches and potholes. Finally, recommendations on maintenance method are provided to guide the Sulaimaniyah governorate and municipality on solving the distresses and to have a promising repairing practice for the road network